Sapa Salah Seleh as Javanese Philosophy of Life: The Perspective of Humanism and Value Education - Sukron Mazid; Farikah; Mimi Mulyani; Atsani Wulansari; Angela Carolina Flores Riquelme (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2026)
The degradation of social ethics, the strengthening of individualism, and the weakening of concern for human values ​​require strengthening character education rooted in local wisdom. One relevant Javanese cultural value is the sapa salah seleh philosophy, which embodies the principles of honesty, moral responsibility, and ethical awareness as a manifestation of humanism in social life. This study aims to examine the humanistic values contained in the sapa salah seleh philosophy and to analyze their relevance for values education in the contemporary era. The study uses a qualitative-descriptive approach with a literature study method. Data were obtained from Javanese cultural texts, local proverbs, and literature on humanism and character education, then analyzed using a hermeneutic approach to interpret the philosophical meaning contained therein. The results show that the sapa salah seleh philosophy embodies humanistic values such as self-awareness, honesty, moral responsibility, empathy, self-control, and respect for others. These values ​​are relevant to strengthening character education because they can encourage the formation of tolerant, empathetic, and responsible attitudes in social life. This finding confirms that integrating the sapa salah seleh philosophy into education can be an alternative for strengthening a humanist character that is contextual and rooted in local culture.